2008
DOI: 10.1002/ange.200705237
|View full text |Cite
|
Sign up to set email alerts
|

Perylenbisimid‐Dimere als fluoreszenter “Klebstoff” für DNA und zum Nachweis von Basenfehlpaarungen

Abstract: Perylen-3,4:9,10-tetracarbonsäurebisimid (PB) und dessen Derivate werden aufgrund ihrer hervorragenden photochemischen Stabilität und der hohen Quantenausbeuten gerne als Fluoreszenzfarbstoffe in organischen Materialien eingesetzt. [1,2] Die starken hydrophoben Wechselwirkungen zwischen den einzelnen PB-Chromophoren machen diesen Farbstoff zu einem wichtigen Baustein für funktionelle supramolekulare Architekturen. [1,3] Betrachtet man die Kombination dieser Eigenschaften, erscheint es interessant, PB in der di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0
14

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 37 publications
2
29
0
14
Order By: Relevance
“…[27,28] The 2'-deoxyribofuranoside of natural nucleosides was replaced by an acyclic linker that is tethered to one of the imide nitrogen atoms of the PB dye. We showed that this linker allows different chromophores to intercalate in the base stack while facilitating the synthesis of the corresponding phosphoramidites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[27,28] The 2'-deoxyribofuranoside of natural nucleosides was replaced by an acyclic linker that is tethered to one of the imide nitrogen atoms of the PB dye. We showed that this linker allows different chromophores to intercalate in the base stack while facilitating the synthesis of the corresponding phosphoramidites.…”
Section: Resultsmentioning
confidence: 99%
“…We showed that this linker allows different chromophores to intercalate in the base stack while facilitating the synthesis of the corresponding phosphoramidites. [27][28][29][30] The S configuration of this linker was chosen to mimic the stereochemical situation at the 3'-position of natural 2'-deoxyribofuranosides. [31][32][33] All synthesized duplexes (DNA1-DNA7) contain palindromic sequences to ensure quantitative duplex formation in the samples for spectroscopic measurements (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perylenediimides (PDIs), which have the advantages of strong absorptivity, high fluorescence quantum yields, high photochemical and thermal stability, strong hydrophobic p-p stacking interactions, and semiconducting properties, have been incorporated in a variety of structures. [4][5][6][7][8][9][10][11][12][13][14][15][16] Recently, Wagner and Wagenknecht [10] reported the preparation of a PDI derivative, P (Figure 1), which is readily incorporated into an oligonucleotide and serves as a base-pair surrogate when located opposite an abasic site in a duplex structure. The incorporation of P in opposite complementary oligonucleotides has been shown to result in the formation of stable duplexes in which the P units are located in a zipperlike fashion within the hydrophobic interior of the resulting duplex.…”
mentioning
confidence: 98%
“…[5,17] The stacking of P units within the duplex resulted in an excimer-like state following photoexcitation. [16] We report herein the results of our investigation of intramolecular electron hopping within a series of synthetic DNA hairpins 1-4 (Figure 1). These hairpins possess compact 3'-CCA loop regions connecting poly(T)-poly(A) stems containing a single P moiety located opposite an abasic site (1), two P moieties located opposite abasic sites and attached either to the same strand (in 2 s) or to opposite strands (in 2 o), or three or four P moieties positioned adjacent to one another but on opposite strands in a zipperlike fashion (in 3 and 4).…”
mentioning
confidence: 99%